2001
DOI: 10.1579/0044-7447-30.8.496
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Evidence of Early Eutrophication and Heavy Metal Pollution of Lake Mälaren, Central Sweden

Abstract: Lake Mälaren is the water supply and recreation area for more than 1 million people in central Sweden and subject to considerable environmental concern. To establish background data for assessments of contemporary levels of trophy and heavy metal pollution, sediment cores from the lake were analyzed. Diatom-inferred lake-water phosphorus concentrations suggest that pre-20th century nutrient levels in Södra Björkfjärden, a basin in the eastern part of Mälaren, were higher (c. 10-20 micrograms TP L-1) than previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…Further, the absence of a defined gradient in sediments deposited prior to ca. 1970, despite elevated ␦ 15 N in L. Mälaren at that time (Renberg et al 2001), indicates that present-day gradients in N isotopes arise from effluent inputs since the initiation of the STP. Thus, we assume that the isotopic gradient in Himmerfjärden primarily reflected a decreasing contribution of effluent N seaward.…”
Section: Delineating Effluent Influence-surface Sediment ␦mentioning
confidence: 92%
See 2 more Smart Citations
“…Further, the absence of a defined gradient in sediments deposited prior to ca. 1970, despite elevated ␦ 15 N in L. Mälaren at that time (Renberg et al 2001), indicates that present-day gradients in N isotopes arise from effluent inputs since the initiation of the STP. Thus, we assume that the isotopic gradient in Himmerfjärden primarily reflected a decreasing contribution of effluent N seaward.…”
Section: Delineating Effluent Influence-surface Sediment ␦mentioning
confidence: 92%
“…The influence of effluent N was most pronounced in the innermost basins, with sedimentary ␦ 15 N values generally above 7‰ within 12 km of the outfall ( Fig. 2A) (Renberg et al 2001). Thus, we cannot rule out the possibility that some transfer of N from L. Mälaren has contributed to the enriched N in sediments near the inlet, although the overall trend indicates that this is only a localized effect.…”
Section: Delineating Effluent Influence-surface Sediment ␦mentioning
confidence: 93%
See 1 more Smart Citation
“…In 2012 wheat, barley, and oat were the dominating crops; however, 33 % of arable land is used for haymaking and pasture, and approximate 10 % lie fallow. Diatom analyses have shown that the lake Mälaren was culturally eutrophicated already in the medieval time (Renberg et al 2001). Phosphorus has been monitored in Lake Mälaren since the 1960s, and the monitoring shows that the introduction of chemical precipitation to the sewage water treatment process led to large improvements in the 1960s and 1970s, reducing the P input to the lake by 60 %.…”
Section: Study Area: Northern Baltic Sea River Basin District (Nbs-rbd)mentioning
confidence: 99%
“…The content of the isotope Cs-137 was established in core 3. The history of SCP presence in sediments is established by Goldberg (1975, 1979), Wik (1992), Odgaard (1993), Rose et al (1990Rose et al ( , 1995Rose et al ( , 1999Rose et al ( , 2001), Bindler et al (2002) and Renberg et al (2001), on which the dating of modern sediments in Karlskärsviken is based.…”
Section: Datingmentioning
confidence: 99%